Mistletoe on Main Street - Miles, Olivia (New York : Forever, 2014)
Briar Creek's quaint shop windows, cozy homes nestled in snow, and neighborly residents are what Christmas dreams are made of--for everyone except Grace Madison. She left her hometown years ago to pursue a writing career. But when her father's death leaves his bookstore empty, Grace must return to face why she fled Vermont in the first place: Luke Hastings, who still heats her up like a shot of smoky whiskey on a cold winter's night.
Includes a preview of A match made on Main Street (p. [365]-376).
Keywords: Authors -- Fiction; Women authors -- Fiction; Christmas stories; Vermont -- Fiction; Love stories